2009
DOI: 10.1007/978-1-4419-1399-9_68
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Phenotyping in the Cone-Specific Photoreceptor Function Loss 1 (cpfl1) Mouse Mutant – A Model of Cone Dystrophies

Abstract: While the absence of substantial light-evoked cone responses in the cpfl1 mice is evident from early on, the course of physical cone degeneration is protracted and has a major drop between PW4 and PW8. However, these changes do not lead to significant alterations in retinal architecture, probably due to the relatively low number and wide dissemination of cone photoreceptor cells within the afoveate mouse retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…RCD is especially debilitating to vision in human patients. However, there are few animal models of cone dystrophy [911]. Our laboratory has discovered and bred CSNB and RCD rat models to prove X-linked recessive inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…RCD is especially debilitating to vision in human patients. However, there are few animal models of cone dystrophy [911]. Our laboratory has discovered and bred CSNB and RCD rat models to prove X-linked recessive inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative analysis of three ACHM mouse models shows that they have a similar progression of cone death, with a sharp peak at roughly the same time around postnatal day 24 (P24) (Michalakis et al 2005;Ding et al 2009;Trifunovic et al 2010), but a continual degeneration was also reported in both the cpfl1 (Fischer et al 2010) and Cnga3…”
Section: Pde6 Deficiency and Cone Cell Death Mechanismsmentioning
confidence: 93%
“…Despite the controversy surrounding cone fate in human patients, in the last few years several ACHM animal models have been described and shown to have active cone degeneration: the Cnga3 naturally-occurring mutant (Pang et al 2010) and knockout mouse models ( Cnga3 -/-) (Biel et al 1999), the Pde6c-deficient cpfl1 mouse and zebrafish models (Stearns et al 2007;Chang et al 2009) and the dog and mouse model of Cngb3 deficiency (Sidjanin et al 2002;Ding et al 2009). Even though the progressive loss of cone photoreceptors was established in several of these models (Michalakis et al 2005;Ding et al 2009;Fischer et al 2010;Trifunovic et al 2010;Xu et al 2011), the precise kinetics of the degeneration has not yet been fully elucidated.…”
Section: Primary Cone Loss In Achromatopsiamentioning
confidence: 98%
“…The Cpfl1 [cone photoreceptor function loss (1)] mouse harbors a 116-bp insertion between exon 4 and 5, as well as an additional 1-bp deletion in exon 7 in the Pde6c gene, leading to an in-frame shift, introducing premature termination codons, the loss of activity of the enzyme, and the accumulation of cGMP [49,88,98]. Cpfl1 mice display the early-onset, rapid/severe cone degeneration phenotype, including the loss of cone function and death of cones [88,[98][99][100].…”
Section: Deficiency Of Pde6mentioning
confidence: 99%